SPAG6 Promotes Multiple Myeloma Through Activation of the MAPK/ERK Signaling Pathway - Li, Junnan; Yan, Xinyu; Ding, Li; Yin, Jiaxiu; Li, Ping; Liu, Lin (Frontiers in Pharmacology, 2025)
BackgroundSperm - associated antigen 6 (SPAG6), a member of the cancer/testis antigen (CTA) family, has been linked to multiple hematologic malignancies. Nevertheless, its role in multiple myeloma (MM) remains unclear.MethodsBioinformatics, tissue specimens from plasma cell tumors, and bone marrow samples of MM patients were utilized to evaluate SPAG6 expression and to analyze its correlations with clinical features and prognosis. In vitro, RNA interference was applied to downregulate SPAG6 in U266 cells and upregulate it in RPMI - 8226 cells, and then its impacts on cell proliferation, apoptosis, and migration were investigated. Transcriptome sequencing data were comprehensively analyzed to elucidate the mechanism of SPAG6 in MM cells.ResultsSPAG6 was positively expressed in MM cell lines, plasma cell tumor tissue specimens, and MM patient bone marrow samples. The mRNA expression of SPAG6 in MM patients was upregulated relative to the control group and was correlated with blood calcium levels, plasma cell ratio, and skeletal infiltration. In vitro, SPAG6 overexpression promoted cell proliferation, migration, and the resistance to apoptosis in MM cells, while down - expression had contrary effects. Mechanistic studies revealed that SPAG6 directly interacts with dual-specificity phosphatase 1 (DUSP1). Furthermore, SPAG6 was found to modulate the expression of downstream proteins in the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) signaling pathway by regulating DUSP1 activity.ConclusionOverall, this study highlights that SPAG6 may serve as a potential therapeutic target for MM by regulating DUSP1 expression to activate the MAPK/ERK signaling pathway.